Excellence in elective hip and knee surgery: what does it look like? A positive deviance approach. Issue 1 (January 2020) - Hughes, Lesley; Sheard, Laura; Pinkney, Lisa; Lawton, Rebecca L
Objectives: Positive deviance is a way of examining variation across health care settings to understand how and why high-performing clinical teams or organizations achieve their results despite facing the same constraints as others. This study explores how exceptional performance is delivered within enhanced hip and knee elective surgery in England. We were particularly interested in non-clinical factors that may influence patient outcomes. Methods: We used 28-day emergency readmissions and patient-reported outcomes to identify two hospitals providing enhanced elective hip and knee replacement surgery and who presented different levels of performance. We used ethnographic observations, in-depth interviews, focus groups and documentary analysis, conducted over eight months. The study involved 54 health care professionals from multiple professional backgrounds. Results: Five key themes were identified, which may underpin the high performance in the site identified as a positive deviant: (i) leadership and engagement that adopts a distributed approach to sustain progress and engage team members; (ii) autonomy, in particular the ability for all clinical staff to make decisions about patient care; (iii) relationships and communication, which promote clear lines of communication and a climate of shared decision making within and across teams; (iv) patient empowerment, which supports patients in managing their behaviour before and after surgery; and (v) resilience, which enables the workforce to respond to threats to maintain high performance such as those that could reduce capacity and flow, or interfere with provision and coordination. Conclusions: Our study demonstrates that it is possible to build an excellent service that meets the needs of the local population and the wider organization agenda despite constraints and rising demands. The findings can inform orthopaedic and other surgical departments on ways in which they can achieve high performance within existing resources.